2020
DOI: 10.1038/s41396-019-0572-z
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovis uses the ESX-1 Type VII secretion system to escape predation by the soil-dwelling amoeba Dictyostelium discoideum

Abstract: Mycobacterium bovis is the causative agent of bovine tuberculosis and the predominant cause of zoonotic tuberculosis in people. Bovine tuberculosis occurs in farmed cattle but also in a variety of wild animals, which form a reservoir of infection. Although direct transmission of tuberculosis occurs between mammals, the low frequency of contact between different host species and abundant shedding of bacilli by infected animals suggests an infectious route via environmental contamination. Other intracellular pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 93 publications
4
17
0
Order By: Relevance
“…Genes classified as ES were congruent between the species and also with existing studies of gene essentiality in M. tuberculosis (21)(22)(23)42). Comparing this study with a previously published M. bovis dataset revealed a 42% overlap which increased when genes predicted to show a GD as a result of the transposon insertion were taken into account (26). There were some indications of differences between the species, and a meta-analysis of the data indicated that 42 genes were differentially essential between the species.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Genes classified as ES were congruent between the species and also with existing studies of gene essentiality in M. tuberculosis (21)(22)(23)42). Comparing this study with a previously published M. bovis dataset revealed a 42% overlap which increased when genes predicted to show a GD as a result of the transposon insertion were taken into account (26). There were some indications of differences between the species, and a meta-analysis of the data indicated that 42 genes were differentially essential between the species.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, the M. tuberculosis dataset generated in our study shared good overlap with other published datasets (Figure 2C). When comparing M. bovis genes classified as ES with those reported by Butler et al (26) we found that 220 (42%) genes were shared between these data sets (Figure 2B). Butler et al reported a total of 318 genes to be essential in M. bovis in vitro prior to selection in Dictyostelium discoideum compared to 527 reported in this study.…”
Section: Comparisons Of Essentiality Between M Bovis Af2122/97 and M Tuberculosis H37rvsupporting
confidence: 52%
See 1 more Smart Citation
“…Similarly, environmental single-celled organisms, such as free-living amoebae (FLA), have long been hypothesised to be a “nursery” for intracellular bacteria within the wider environment [ 5 ], perhaps even having been the hosts in which nonpathogenic bacteria transitioned to become pathogens [ 100 ]. Recent experimental evidence confirms that survival within FLA hosts occurs [ 101 ], using the same mechanisms employed to persist in vertebrate macrophages. Furthermore, exposure of laboratory animals to infected FLA can lead to transmission of pulmonary TB [ 102 ].…”
Section: How Might the Environment Become Contaminated By mentioning
confidence: 78%
“…The team found that, unlike other bacteria which are ingested/phagocytosed by amoebae and degraded, M . bovis survived intracellularly, using the same molecular methods of host evasion it deploys so effectively in host macrophages [ 101 ]. Furthermore, the bacillus was able to transmit to other amoebae and replicate at ambient/environmental temperature (25°C), something that was unexpected for an organism thought to be adapted to behave optimally in a vertebrate host environment of ∼37°C [ 101 ].…”
Section: Methods For Investigating M mentioning
confidence: 99%